Amyloid β-induced impairments on mitochondrial dynamics, hippocampal neurogenesis, and memory are restored by phosphodiesterase 7 inhibition - Fernando Bartolome; Macarena de la Cueva; Consuelo Pascual; Desiree Antequera; Tamara Fernandez; Carmen Gil; Ana Martinez; Eva Carro (Alzheimer’s Research & Therapy, 2018)
Abstract Background The phosphodiesterase (PDE) 7 inhibitor S14 is a cell-permeable small heterocyclic molecule that is able to cross the blood–brain barrier. We previously found that intraperitoneal treatment with S14 exerted neuroprotection in an Alzheimer’s disease (AD) model (in APP/PS1 mice). The objective of this study was to investigate the neurogenic and cellular effects of oral administration of S14 on amyloid β (Aβ) overload. Methods We orally administered the PDE7 inhibitor S14 (15 mg/kg/day) or vehicle in 6-month-old APP/PS1 mice. After 5 weeks of S14 treatment, we evaluated cognitive functions and brain tissues. We also assessed the effects of S14 on the Aβ-treated human neuroblastome SH-SY5Y cell line. Results Targeting the cyclic adenosine monophosphate (cAMP)/cAMP-response element binding protein (CREB) pathway, S14 rescued cognitive decline by improving hippocampal neurogenesis in APP/PS1 transgenic mice. Additionally, S14 treatment reverted the Aβ-induced reduction in mitochondrial mass in APP/PS1 mice and in the human neuroblastoma SH-SY5Y cells co-exposed to Aβ. The restoration of the mitochondrial mass was found to be a dual effect of S14: a rescue of the mitochondrial biogenesis formerly slowed down by Aβ overload, and a reduction in the Aβ-increased mitochondrial clearance mechanism of mitophagy. Conclusions Here, we show new therapeutic effects of the PDE7 inhibitor, confirming S14 as a potential therapeutic drug for AD.